2004
DOI: 10.1002/pds.936
|View full text |Cite
|
Sign up to set email alerts
|

Safety of anthrax vaccine: an expanded review and evaluation of adverse events reported to the Vaccine Adverse Event Reporting System (VAERS)

Abstract: This review produced no evidence for an unusual rate of any SAE or OMIAE attributable to AVA. It supported an earlier impression that AVA may cause significant local inflammation and should be administered over the deltoid rather than the triceps to avoid direct or compression injury to the ulnar nerve. The subjects of VAERS reports tended to be older than all recipients of AVA. Females generally had and/or reported AEs more often than males, but transient articular reactions were surprisingly more common in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 13 publications
5
36
0
Order By: Relevance
“…No mechanism for this activity has been proposed. Over 1.4 million people have been vaccinated with AVA, and studies have demonstrated the vaccine to be safe [32][33][34]. In spite of these facts, there remains significant resistance to AVA among military personnel and the public at large.…”
Section: Discussionmentioning
confidence: 99%
“…No mechanism for this activity has been proposed. Over 1.4 million people have been vaccinated with AVA, and studies have demonstrated the vaccine to be safe [32][33][34]. In spite of these facts, there remains significant resistance to AVA among military personnel and the public at large.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized survey instruments were used in the questionnaire for comparability. Sources included the Chicago Reproductive Health Survey (National Institute of Environmental Health Sciences, Research Triangle Park, NC, 1991), the National Survey on Family Growth, Cycle IV [42], and the National Maternal and Infant Health Survey [43]. Miscarriages/spontaneous abortions were defined as fetal deaths occurring before 22 weeks gestation, while stillbirths were defined as fetal deaths occurring after 22 weeks gestation.…”
Section: Study Populationmentioning
confidence: 99%
“…This vaccine has been shown to confer good protection in humans (6), but it is a fairly undefined formulation and requires a 6-injection dosing regimen. Furthermore, there has been an ongoing debate about its safety, although large trials of the vaccine have indicated an acceptable safety level (7,8). As a result of these considerations, several approaches to a second generation vaccine are in development, the majority of which target PA.…”
mentioning
confidence: 99%